Radiation and Stemness Phenotype May Influence Individual Breast Cancer Outcomes: The Crucial Role of MMPs and Microenvironment - Olivares-Urbano, María Auxiliadora (Cancers (Basel), 2019)
Breast cancer is the most common cancer in women. Radiotherapy (RT) is one of the mainstay treatments for cancer but in some cases is not effective. Cancer stem cells (CSCs) within the tumor can be responsible for recurrence and metastasis after RT. Matrix metalloproteases (MMPs), regulated mainly by tissue inhibitors of metalloproteinases (TIMPs) and histone deacetylases (HDACs), may also contribute to tumor development by modifying its activity after RT. The aim of this work was to study the effects of RT on the expression of MMPs, TIMPs and HDACs on different cell subpopulations in MCF-7, MDA-MB-231 and SK-BR-3 cell lines. We assessed the in vitro expression of these genes in different 3D culture models and induced tumors in female NSG mice by orthotopic xenotransplants. Our results showed that gene expression is related to the cell subpopulation studied, the culture model used and the single radiation dose administered. Moreover, the crucial role played by the microenvironment in terms of cell interactions and CSC plasticity in tumor growth and RT outcome is also shown, supporting the use of higher doses (6 Gy) to achieve better control of tumor development.